The Effect of Shuttle Run Training on Dribbling Speed in Futsal Games for Students of SMPN 06 Palembang - Tiara Nabila; Farizal Imansyah; Daryono Daryono (IJRAEL: International Journal of Religion Education and Law, 2022)
The purpose of this study was to determine: (1) the effects of exercise to the shuttle-run ball kecepatan skills in the students of Emmanuel SSB, (2) the effects of exercise zig-zag to the ball kecepatan skills in the students of Emmanuel SSB, (3) the exercise that more effective in improving the ability of kecepatan the ball in the students of Emmanuel SSB. The results of this research was (1) There is an effect of exercise Shuttle-run to the kecepatan skills in the students of Emmanuel SSB of aged 13-15; (2) There is an effect of exercise Zig-zag to kecepatan skills in the students of Emmanuel SSB of aged 13-15; (3) Exercise with the Zig- zag method was more effective in improving the ability of kecepatan the ball in the students of Emmanuel SSB.